Analisis Store Environment dan Emosi Positif terhadap Impulse Buying - Ayi Muhyidin; Erry Sunarya; Asep M. Ramdan (IPM2KPE, 2019)
The purpose of this study was to analysis the effect of store environment and positive emotions on impulse buying in the cafe. The method used in this study is the use the type of probability sampling includes in the simple random sampling. The sample used in this research was 100 respondents and data collection methods using a questionnaire. The analysis technique using validity test, reliability test, multiple linear regression analysis, including test coefficient of determination, multiple correlation coefficient, simultaneous test (F test), and partial test (T test). The results of the test coefficient of determination seen from value (Adjusted R2) of 0,425 can be interpreted that the effect of Store Environment and Positive Emotions on Impulse Buying is 42,5%. The remaining 57,5% is influenced by other factors not explained in this study. Based on the multiple correlation coefficient test seen from the R value of 0.661, it shows that there is a strong relationship between store environment and positive emotions with impulse buying. Based on the F test the probability value sig. 0,000 <0,10, which means that together Store Environment (X1) and Positive Emotions (X2) significantly influence Impulse Buying (Y). Conclusion, based on the t test showing Store Environment (X1) has a significant effect on Impulse Buying (Y), Positive Emotions (X2) has a significant effect on Impulse Buying (Y). Keyword : Store Environment, Positive Emotions, Consumer Satisfactio